A spin-wave resonance study on reentrant Ni77Mn23 thin films - Ozdemir, M; Aktas, B; Oner, Y; Sato, T; Ando, T (Elsevier Science Bv, 1996)
The magnetic properties of thin (300 Angstrom) reentrant Ni77Mn23 films grown on a quartz substrate using the electron beam evaporation technique have been investigated. The spin-wave resonance (SWR) technique has been used to study the exchange parameter D and magnetic anisotropies as a function of temperature between 4 and 300 K. The SWR spectra exhibit directional character upon cooling the sample in an external field H-c, which is a sign of a spin-glass property. At higher temperatures, in addition to the dominant surface SWR mode, there is a much weaker bulk mode on the lower field side. Using a uniaxial surface and effective bulk anisotropy together we simulated the experimental spectra and deduced the surface anisotropy and magnetic stiffness parameters as a function of temperature. The sample shows an easy plane surface anisotropy. Both the exchange and anisotropy parameters increase when the temperature is in the spin-glass regime. Furthermore, the surface anisotropy energy dominates the overall magnetic behavior of this system.
Keywords: spin-wave resonance; ferromagnetism; reentrant; thin films; surface anisotropy